Extent, Type and Reasons for Adaptation and Modification When Scaling-Up an Effective Physical Activity Program: Physical Activity 4 Everyone (PA4E1) - Mclaughlin, Matthew; Campbell, Elizabeth; Sutherland, Rachel; McKenzie, Tom; Davies, Lynda; Wiggers, John; Wolfenden, Luke (Frontiers in Health Services, 2021)
Background: Few studies have described the extent, type and reasons for making changes to a program prior to and during its delivery using a consistent taxonomy. Physical Activity 4 Everyone (PA4E1) is a secondary school physical activity program that was scaled-up for delivery to a greater number of schools. We aimed to describe the extent, type and reasons for changes to the PA4E1 program (the evidence-based physical activity practices, implementation support strategies and evaluation methods) made before its delivery at scale (adaptations) and during its delivery in a scale-up trial (modifications). Methods: The Framework for Reporting Adaptations and Modifications-Enhanced (FRAME) was used to describe adaptations (planned and made prior to the scale-up trial) and modifications (made during the conduct of the trial). A list of adaptations was generated from a comparison of the efficacy and scale-up trials via published PA4E1 protocols, trial registrations and information provided by trial investigators. Monthly trial team meetings tracked and coded modifications in “real-time” during the conduct of the scale-up trial. The extent, type and reasons for both adaptations and modifications were summarized descriptively. Results: In total, 20 adaptations and 20 modifications were identified, these were to physical activity practices (n = 8; n = 3), implementation support strategies (n = 6; n = 16) and evaluation methods (n = 6, n = 1), respectively. Few adaptations were “fidelity inconsistent” (n = 2), made “unsystematically” (n = 1) and proposed to have a “negative” impact on the effectiveness of the program (n = 1). Reasons for the adaptations varied. Of the 20 modifications, all were “fidelity consistent” and the majority were made “proactively” (n = 12), though most were “unsystematic” (n = 18). Fifteen of the modifications were thought to have a “positive” impact on program effectiveness. The main reason for modification was the “available resources” (n = 14) of the PA4E1 Implementation Team. Conclusions: Adaptations and modifications to public health programs are common. Modifications have the potential to impact the implementation and effectiveness of programs. Our findings underscore the importance of comprehensive reporting of the extent, type and reasons for modifications as part of process evaluations, as this data may be important to the interpretation of trial findings. Clinical Trial Registration:https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372870, Identifier ACTRN12617000681358.